The superpowers playground : Djibouti and geopolitics of the Indo-Pacific in the 21st century - Gurjar, Sankalp (Oxon : Routledge, 2023)
"This book analyses the evolving geopolitics in the Indo-Pacific region and explains how Djibouti fits in the global strategies of four major powers-the US, China, Japan, and France."--
Keywords: Political geography; Geopolitics